Industrial agriculture and ape conservation - Rainer, Helga; White, Alison (Alison R. T.); Lanjouw, Annette; Arcus Foundation (Cambridge : Cambridge University Press, 2015)
Social and economic systems worldwide are changing rapidly. These changes are accompanied by an increasing demand for natural resources, including land, water, minerals, energy sources, food and timber. Today's foremost challenge lies in finding the tools to address the complexity of these interrelated trends, and in implementing strategies to balance environmental and socioeconomic needs. This volume contributes to this search by presenting original research, topical case studies and emerging best practice from a range of key stakeholders to examine the interface between ape conservation and industrial agriculture. In assessing the drivers behind agricultural expansion and land investments, it sheds light on governance challenges and legal frameworks that shape land use. Intended for policy makers, industry experts, decision makers, academics, researchers and NGOs, it is designed to inform debate, practice and policy to help reconcile the goals of industrial agriculture with those of ape conservation and welfare, and social and economic development.
Title from publisher's bibliographic system (viewed on 20 Jul 2016).
Open Access title.
Keywords: Apes -- Conservation; Agriculture -- Environmental aspects; Apes -- Effect of human beings on